THE ROLE OF WORK-LIFE BALANCE IN JOB SATISFACTION: A CASE STUDY OF UZBEKISTAN’S IT INDUSTRY (International Conference on Education and Innovation, 2025)
The current research analyzes the relationship between work-life balance (WLB) and job satisfaction in the context of the growing information technology (IT) sector in Uzbekistan. As the digitization shift is on the rise, IT specialists are under heightened pressure which can lead to struggles in their work-life balance. This study outlines major components of WLB, such as remote work options, intra-company workload distribution, flexible working hours, and other organizational support services.A combination of strategies design was used, which included questionnaires, open-ended interviews, and case analysis to evaluate job satisfaction of IT employees. Findings also suggest that stress, low productivity, and high turnover rates, brought about by negative WLB, are harmful at the individual level as well as the organizational level. On the other hand, organizations that adopt flexible work arrangements, train organizational psychologists, and integrate workload management can increase retention and engagement levels among employees.In addition, this study develops a quantitative model of job satisfaction that is defined by WLB elements contributing to the assessment of employee QWL within an organization for systematic improvement purposes. The study results provide IT companies with specific suggestions on how to deal with WLB policies for better employee productivity.